Framework : the journal of cinema and media - Sankofa Film & Video.; University of East Anglia. School of English and American Studies.; University of Warwick Arts Federation. (University of Warwick Arts Federation, 1975)
Published: University of Warwick Arts Federation, 1975-spring 1979; School of English and American Studies, University of East Anglia, autumn 1980-spring 1981; London : Sankofa Film & Video Ltd., Unit K, 1992-; Detroit : Wayne State University Press, 1999-Current frequency: 2/year.